HUBUNGAN KEMAMPUAN RESILIENSI SISWA BROKEN HOME DENGAN MOTIVASI BELAJAR DI MAN 2 YOGYAKARTA - Hariyanti, Tri; Prasetyoaji, Ari; Feni, Muhamad (STAI Syubbanul Wathon Magelang, 2024)
Broken home is defined as a family that is fractured, not harmonious and does not work like a harmonious and peaceful family. The condition of a broken home family encourages children to have resilience skills in living life. Students who are in a disharmonious family environment will have an impact on themselves, one of which is a lack of motivation to learn. This study aims to determine the relationship between the resilience abilities of broken home students and their learning motivation at MAN 2 Yogyakarta. This study uses a quantitative approach with correlational methods. Data analysis technique using pearson product moment correlation. The population in this study were all broken home students in class X and XI MAN 2 Yogyakarta, consisting of 31 students. The research results obtained p = 0.003<0.05, so H0 was rejected and H1 was accepted. The correlation coefficient of 0.521 is positive in the range 0.40-0.599 in the medium category. The results obtained indicate that there is a significant relationship between resilience abilities and the learning motivation of broken home students at MAN 2 Yogyakarta with a moderate level of relationship.